ENHANCING STUDENTS’ MASTERY OF THE FOUR ENGLISH SKILLS THROUGH THE DRILL METHOD AT LKP YHSUA TRAINING INSTITUTE FOR SELF-DEVELOPMENT - Halitopo, Manase; Kogoya , Napius; Maitimu , Laura Sansa (PT. Jurnal Center Indonesia Publisher, 2025)
The international language nowadays is English. To make learning more enjoyable and fun for students, the right approach is required. The researcher aims to explain the drilling method to enhance the students’ English skills. In this research, the researchers used a qualitative descriptive study as the research methodology. The study takes place at the LKP YHSUA Training Institute for Self-Development, involving 20 students. The data was collected through observation, interview, and documentation. The data analysis was done through data collection, reduction, display, and drawing conclusions. The results showed that the drilling method used became the suitable method that has a significant effect on the young learners’ mastery of the four English skills. In addition, the young learners can pronounce, read, write, and listen to the whole lessons and games given through the use of the drilling method combined with printed stories through learning process. Besides that, teaching and learning process becomes more fun. Overall, the drilling method has proven to be an effective approach for teaching the four English skills to students.